2014
DOI: 10.1002/2014ja020284
|View full text |Cite
|
Sign up to set email alerts
|

Seismo‐ionospheric coupling appearing as equatorial electron density enhancements observed via DEMETER electron density measurements

Abstract: International audienceWe report the processes and results of statistical analysis on the ionospheric electron densitydata measured by the Detection of Electro-Magnetic Emissions Transmitted from Earthquake Regions(DEMETER) satellite over a period of 6 years (2005–2010), in order to investigate the correlation betweenseismic activity and equatorial plasma density variations. To simplify the analysis, three equatorial regionswith frequent earthquakes were selected and then one-dimensional time series analysis be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 60 publications
(58 reference statements)
1
23
0
Order By: Relevance
“…This can be due to the fact that the previous analyses were done at different locations in the ionosphere by sounders or using the TEC, which is an integrated parameter. However, Ryu et al () have shown that EIA was enhanced from approximately 2 weeks before to a few days after the occurrence of very large earthquakes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be due to the fact that the previous analyses were done at different locations in the ionosphere by sounders or using the TEC, which is an integrated parameter. However, Ryu et al () have shown that EIA was enhanced from approximately 2 weeks before to a few days after the occurrence of very large earthquakes.…”
Section: Discussionmentioning
confidence: 99%
“…Another statistical study of ionospheric perturbations in relation with equatorial anomalies observed by DEMETER has been done by Hobara et al (2013) using the electric field measurement, who have shown a weak correlation between nighttime ionospheric perturbations and land earthquakes. A similar work by Ryu et al (2014) investigated the correlation between seismic activity and equatorial plasma density variations. They indicate that equatorial ionization anomaly (EIA) enhancements can be correlated with earthquakes of large magnitude (M > 5.0), which seems to support the early work by Molchanov et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…Following this EQ (marked as A in the figure), two other EQs (B and C) occurred. We define NEPD (Normalized Equatorial Plasma Density) as Ne eq /Ne mid , as proposed by Ryu et al (2014b). Ne eq is over geomagnetic equator, and Ne mid is the average of Ne in mid-latitude of both hemispheres.…”
Section: Demeter Data Analysismentioning
confidence: 99%
“…Recently, reports based on satellite data have started to appear (Parrot et al 2006;Oyama et al 2008Oyama et al , 2011Akhoondzadeh et al 2010;Ryu et al 2014b). Zakharenkova et al (2007) studied the Hokkaido EQ which occurred on September 25, 2003 (M = 8.3) using TEC along with individual satellite passes.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in the previous studies that dense GPS arrays can provide an opportunity to investigate ionospheric perturbations in the most efficient manner (Reddy, 2016;Reddy and Seemala, 2015;Seemala and Valladares, 2011;Ogawa et al, 2012;Sunil et al, 2015;Heki, 2013, 2015). Some advanced techniques, such as HF Doppler sounding (Artru et al, 2004;Ogawa et al, 2012), DEMETER (Ryu et al, 2014), Over-The-Horizon Radar (Occhipinti et al, 2010), Faraday rotation measurements using linearly polarized electromagnetic signals from geostationary satellites (Davies, 1980), and GPS (Ducic et al, 2003;Heki, 2011;Saito et al, 2011) have also shown that ionospheric plasma perturbations can be generated by large earthquakes. Study of seismo-ionospheric response of earthquakes from 1965 to 2013, have shown that only earthquakes of Mw ≥ 6.5 generate significant wave response in the ionosphere (Perevalova et al 2014).…”
Section: Introductionmentioning
confidence: 99%